2014
DOI: 10.5455/ijmsph.2014.170420142
|View full text |Cite
|
Sign up to set email alerts
|

Profile of homicidal death cases at Government Medical College and New Civil Hospital, Surat

Abstract: Background: Surat is one of the fastest growing cities in Asia, situated in the southern region of the Gujarat state of India. Homicidal crimes are one of darkest & inevitable part of any society. We analyzed the current trend of homicidal crimes in Surat in this epidemiological study. Aims & Objective: To analyze various demographic, social and forensic aspects of homicidal crimes in Surat. Materials and Methods: Profiles of total 119 homicidal autopsy cases studied retrospectively, which were conducted durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The rural population is more present as the educational status varies among the rural and urban population, which leads to variation in the crime graph. The findings are similar with the studies conducted by Mittal et al [20] and Zanzrukiya et al [21], where the area of study was more Hindu population.…”
Section: Basra and Singhsupporting
confidence: 91%
“…The rural population is more present as the educational status varies among the rural and urban population, which leads to variation in the crime graph. The findings are similar with the studies conducted by Mittal et al [20] and Zanzrukiya et al [21], where the area of study was more Hindu population.…”
Section: Basra and Singhsupporting
confidence: 91%
“…Sex ratios were lower in studies done by Hugar BS et al 5 (2.53:1), Zankuriya K et al 14 (2.6:1), Singh OG et al 22 (2.85:1) and Mishra PK et al 17 (2.9:1).…”
Section: Discussionmentioning
confidence: 77%
“…Two years study by Shah JP et al in 13 Rajkot region reported that homicide deaths account for 2.70% of all autopsies. In Surat district, Zankuriya K et al 14 studied 119 (2.79%) cases of homicide out of 4264 autopsies over 2 years from 2011-2012.…”
Section: Discussionmentioning
confidence: 99%
“…72 In majority of cases, preferred method of killing used by the miscreants was by inflicting mechanical injury, which is in accordance with the studies reported from Surat and Bangalore. [73][74][75] In sixty percent of the mechanical injury linked homicide preferred choice of weapon was sharp weapon. The increasing use of sharp cutting weapons by the people of this region could well be explained by the fact that these weapons are more dangerous than blunt weapons and are easily available due to agricultural background and at the same time non availability of firearms.…”
Section: Resultsmentioning
confidence: 99%